2007
DOI: 10.1103/physrevc.76.054602
|View full text |Cite
|
Sign up to set email alerts
|

Elastic magnetic form factors of exotic nuclei

Abstract: How to identify the orbital of the valence nucleon(s) of exotic nuclei is an important problem. The elastic magnetic electron scattering is an excellent probe to determine the valence structure of odd-A nuclei. The relativistic mean-field theory has been successfully applied to systematic studies of the elastic charge electron scattering from even-even exotic nuclei. The extension of this method to investigate the elastic magnetic electron scattering from odd-A exotic nuclei is a natural generalization. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
(92 reference statements)
0
16
0
Order By: Relevance
“…In summary, we have found that the geometrical factors in the deformed formalism reduce the multipoles with respect to the spherical ones and help to improve the agreement with experiment in all the deformed cases studied. These reduction factors appear naturally in the deformed formalism, whereas they have to be introduced ad hoc to fit the data in other approaches [21,33]. Collective effects manifest mainly at low-q values through M1 rotational multipoles.…”
Section: B Deformed Nucleimentioning
confidence: 99%
“…In summary, we have found that the geometrical factors in the deformed formalism reduce the multipoles with respect to the spherical ones and help to improve the agreement with experiment in all the deformed cases studied. These reduction factors appear naturally in the deformed formalism, whereas they have to be introduced ad hoc to fit the data in other approaches [21,33]. Collective effects manifest mainly at low-q values through M1 rotational multipoles.…”
Section: B Deformed Nucleimentioning
confidence: 99%
“…The ergodicity of the eigenstates of certain (non-random) multi-body Hamiltonians was also investigated in the context of understanding thermalization [23,29,30]. Much more recently it was shown by Popescu, Short and Winter [31], and Goldstein et al [32] (see also [33][34][35][36][37]), that almost every pure state within a narrow energy band will behave as the microcanonical ensemble, from which it follows that random states will have the same property. Since almost all states have this ergodic property, states that do are called typical states.…”
Section: Introductionmentioning
confidence: 99%
“…We shall mainly focus on calculating the component responses of the upper component, the lower component, and the crossed term of the relativistic bound single-nucleon wave functions of the spin-orbit partner states to elastic magnetic electron scattering and discussing the relative importance of the roles played by the components of the spin-orbit Dirac-4 spinors in elastic magnetic electron-nucleus scattering process accordingly. In addition, the expression of the form factors given in [17] shows that the total transverse response function can also be separated into the component resulting from the spin-related current transition density and the one resulting from the convection current transition density, so we also hope that the research can reveal a little more about the relation between the current transition densities and the corresponding responses in elastic magnetic electron scattering.…”
Section: Introductionmentioning
confidence: 98%
“…According to the models used, there can be a couple of different methods to calculate the form factors [1][2][3][4][5][11][12][13][14][15][16], and each method has its own advantage in revealing the relation between the model and the experimental data. In an earlier publication [ 17], we calculated the elastic magnetic form factors within the relativistic single particle nuclear shell model based on the results given in Refs. [1,[18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation